2021
DOI: 10.1158/2767-9764.crc-21-0067
|View full text |Cite
|
Sign up to set email alerts
|

The ADAM17-directed Inhibitory Antibody MEDI3622 Antagonizes Radiotherapy-induced VEGF Release and Sensitizes Non–Small Cell Lung Cancer for Radiotherapy

Abstract: The cellular response to ionizing radiation (IR) depends on tumor cell and microenvironmental factors. Here, we investigated the role of IR-induced ADAM17 matrix metalloproteinase activity for the intercellular communication between tumor cells and the tumor vasculature in non–small cell lung cancer (NSCLC) tumor models. Factors shed by ADAM17 from NSCLC tumor cells (A549, H358) and relevant for endothelial cell migration were investigated using transwell migration assays, ELISA, and flow cytometry. Tumor angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…In addition, iRhom2, as a key binding protein for ADAM17, further promotes KRAS-induced tumor cell growth by modulating the release of ERBB ligands (196). However, the efficacy of radiotherapy for non-small cell lung cancer was enhanced when blockade of ADAM17 function with the neutralizing antibody (197). These findings suggest that ADAM17 is a cancer-promoting gene and a potential target for anti-lung cancer therapies.…”
Section: Adam17 In Lung Cancermentioning
confidence: 99%
“…In addition, iRhom2, as a key binding protein for ADAM17, further promotes KRAS-induced tumor cell growth by modulating the release of ERBB ligands (196). However, the efficacy of radiotherapy for non-small cell lung cancer was enhanced when blockade of ADAM17 function with the neutralizing antibody (197). These findings suggest that ADAM17 is a cancer-promoting gene and a potential target for anti-lung cancer therapies.…”
Section: Adam17 In Lung Cancermentioning
confidence: 99%
“…Doxycycline-treated cells were seeded into the inserts and starved in 0.5% FBS containing cell growth media. Cell migration towards growth media supplemented with 1.0% FBS was quantified 48 hours following sham-irradiation or irradiation of the inserts with the sublethal dose of 5 Gy ( 21 ). Basal cell migration of NCI-H358 control cells was enhanced in response to irradiation, while basal and IR-enhanced migration was strongly abrogated in EphA2 knockdown cells ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported that IR-induced endothelial cell migration is strongly mediated by tumor cell-located ADAM17 ( 19 , 21 ). In subcutaneous and orthotopic lung tumor models, ADAM17 inhibition by the novel ADAM17-specific therapeutic antibody MEDI3622 in combination with radiotherapy induced a strong anti-angiogenic effect and tumor shrinkage ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations